The influence of montmorillonite on the flame‐retarding properties of intumescent bio‐based PLA composites. Issue 22 (15th February 2022) - Martins, Raíssa Carvalho; Ribeiro, Simone Pereira da Silva; Nascimento, Regina Sandra Veiga; Nascimento, Marco Antonio Chaer; Batistella, Marcos; Lopez‐Cuesta, José‐Marie
Abstract: Biobased flame‐retardant polylactic acid composites were prepared using ammonium polyphosphate (AP), lignin, and a raw montmorillonite (ANa) as the intumescent formulation. The concentration of AP and of ANa was varied in order to study its influence on the flammability properties of the composites. The samples were submitted to cone calorimeter test, thermogravimetric analysis coupled to Fourier‐transform infrared spectroscopy (TGA‐FTIR), limiting oxygen index (LOI), and UL‐94 vertical burn. The cone calorimeter residues were analysed through scanning electronic microscopy, X‐ray diffraction, and FTIR. The results show that the combined addition of the intumescent formulation and the ANa leads to an improvement in the fire behavior of the composites, compared with that of the neat polymer. The best fire‐retardant performance was achieved by using the highest AP concentration (17%) and the lowest ANa concentration (1.2%), reaching a LOI value of 39%. Abstract :